Effect of urolithin A on the improvement of vascular endothelial function depends on the gut microbiota - Nishimoto, Yuichiro; Fujisawa, Kota; Ukawa, Yuichi; Kudoh, Masatake; Funahashi, Kazuki; Kishimoto, Yoshimi; Fukuda, Shinji (Frontiers in Nutrition, 2023)
Background: Urolithin A (UA) is a metabolite produced by gut microbiota from ingested ellagic acid. Although the effect of ellagic acid intake on vascular endothelial function (VEF) improvement has been reported, the effect of UA intake on VEF improvement remains obscure. In addition, UA has been reported to improve the intestinal barrier function, and UA may have improved VEF by gut microbiome alteration. Objective: In this study, we conducted a clinical trial to explore and analyze the effects of UA intake on vascular endothelial function (VEF) and characteristics of the intestinal environment, such as gut microbiome profiling and organic acid composition. Methods: A placebo-controlled, randomized, double-blinded, parallel group trial was conducted on participants who could metabolize small amounts of UA from ellagic acid (non-UA producers) and had relatively poor VEF. VEF was assessed using the flow-mediated vasodilatation (FMD) score. Participants were administered placebo, UA 10 mg/day, or UA 50 mg/day for 12 weeks. FMD was measured and fecal samples were collected at 0, 4, 8, and 12 weeks of treatment. Gut microbiome analysis and organic acid level measurements were performed to evaluate the effects of UA intake on the intestinal environment. This clinical trial is publicly registered at the UMIN-CTR, trial number: UMIN000042014. Results: The gut microbiota of the UA 50 mg/day group showed a significant increase in alpha diversity (Faith’s phylogenetic diversity). Four and nine microbial genera were significantly altered in the UA 10 mg/day and UA 50 mg/day groups, respectively (p < 0.05, not corrected). Participants whose FMD scores improved with UA intake had poor baseline FMD values as well as a low Bacillota/Bacteroidota ratio. Conclusions: UA intake alters the gut microbiota and improves their alpha diversity. In addition, the effect of UA on VEF correlated with the individual gut microbiota. Our results have practical implications for a new approach to providing healthcare that focuses on intestinal environment-based diet therapy.